2017
DOI: 10.1007/s12265-017-9751-3
|View full text |Cite
|
Sign up to set email alerts
|

A Swine Model of Percutaneous Intracoronary Ethanol Induced Acute Myocardial Infarction and Ischemic Mitral Regurgitation

Abstract: Ischemic mitral regurgitation (IMR) is a frequent complication after a myocardial infarction (MI), which doubles mortality. Transcatheter mitral repairs are emerging as alternative treatment options to open heart surgery for IMR, but animal models to test them are lacking. We report a percutaneous swine model of IMR. Seventeen swine were randomized to (group 1, n = 12) MI causing IMR, and (group 2, n = 5) controls. In group 1, MI was induced via percutaneous ethanol injection into the obtuse marginal branches … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Myocardial infarction in the posterior papillary muscle region can lead to displacement of the papillary muscles, which can itself cause mitral regurgitation. The target vessels for ischaemic mitral regurgitation are OM1, OM2, OM3, or OM4 in the left circumflex coronary artery [ 33 ], in some cases including the posterior descending branch of the right coronary artery [ 19 ]. This process can be completed by injecting procoagulant material into the target vessel under intervention [ 33 ] or ligating the coronary artery [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Myocardial infarction in the posterior papillary muscle region can lead to displacement of the papillary muscles, which can itself cause mitral regurgitation. The target vessels for ischaemic mitral regurgitation are OM1, OM2, OM3, or OM4 in the left circumflex coronary artery [ 33 ], in some cases including the posterior descending branch of the right coronary artery [ 19 ]. This process can be completed by injecting procoagulant material into the target vessel under intervention [ 33 ] or ligating the coronary artery [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The target vessels for ischaemic mitral regurgitation are OM1, OM2, OM3, or OM4 in the left circumflex coronary artery [ 33 ], in some cases including the posterior descending branch of the right coronary artery [ 19 ]. This process can be completed by injecting procoagulant material into the target vessel under intervention [ 33 ] or ligating the coronary artery [ 19 ]. Because of the variation of the coronary artery distribution, the myocardial infarction area is uneven after the blood flow is interrupted.…”
Section: Discussionmentioning
confidence: 99%
“…Early work using large animals primarily centered around ischemic modeling, as coronary vasculature ligation or percutaneous ethanol injection provides straightforward mechanisms for inducing targeted infarction and subsequent ischemia (100)(101)(102)(103)(104). In studying ischemic valvular biomechanics, researchers have used these models to analyze a wide variety of phenomena such as ischemic remodeling of MV annular dynamics, surgical techniques, such as posterior leaflet augmentation and chordal cutting, the relationship between ischemic MR and ventricular remodeling, and the effects of annuloplasty ring selection and sizing for ischemic MR repair (102,103,(105)(106)(107)(108)(109)(110)(111)(112)(113). While studies such as these have shown the power of in vivo modeling capabilities, there are some key limitations with this line of research.…”
Section: In Vivo Modelingmentioning
confidence: 99%
“…This model is therefore reasonable for investigations of drug effects on the gastrointestinal tract. Other relevant models include induction of cardiac tamponade, direct aortic, or mesenteric in-flow restriction and open-and closed-chest models of acute cardiac ischemia (15,(22)(23)(24)(25)(26). However, in this study, the intention was to induce and maintain a predetermined level of CO, which was accomplished, to isolate peripheral vasoactive effects from inotropy.…”
Section: The Experimental Modelmentioning
confidence: 99%